2023
DOI: 10.1111/opo.13183
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of optometrists' referral accuracy and contributing factors: A review

Abstract: PurposeIn the UK, ophthalmology has the highest number of outpatient appointments within the National Health Service. False‐positive referrals from primary care are one of the main factors contributing to the oversubscription of hospital eye services (HESs). We reviewed the accuracy of referrals originating from primary care optometrists and contributing factors, such as condition type and years since registration.Recent findingsOf the 31 studies included in the review, 22 were retrospective analyses of referr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…In a quantitative systematic review of optometrists' referral accuracy and the contributing factors, we found significant variation in reported referral accuracy both within and across different ocular conditions. 5 …”
Section: Introductionmentioning
confidence: 99%
“…In a quantitative systematic review of optometrists' referral accuracy and the contributing factors, we found significant variation in reported referral accuracy both within and across different ocular conditions. 5 …”
Section: Introductionmentioning
confidence: 99%